Q: What is 3n divided by 1?

Write your answer...

Submit

Related questions

3n^4 divided by 3n^3 = n

3n+2 + (3n+3 - 3n+1) = 3n+1+1 + (3n+1+2 - 3n+1) = 3*3n+1 + (9*3n+1 - 3n+1)= (3+9-1)*3n+1 = 11*3n+1.

3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6

3n-2w and how do you work it out = 1

5

No. 3n isn't a factor of 3n + 7. The GCF of 3n + 7 and 9n is 1.

In 3n-1 equals 11, n is 4.3n - 1 = 113n - 1 + 1 = 11 + 13n = 123n/3 = 12/3n = 4

Thrice is three, "a number" can be shown as n. This is 3n. 3n/3=n

15-3n=n-1

The remainder is 0.If A has a remainder of 1 when divided by 3, then A = 3m + 1 for some integer mIf B has a remainder of 2 when divided by 3, then B = 3n + 1 for some integer n→ A + B = (3m + 1) + (3n + 2)= 3m + 3n + 1 + 2= 3m + 3n + 3= 3(m + n + 1)= 3k where k = m + n + 1 and is an integer→ A + B = 3k + 0→ remainder when A + B divided by 3 is 0-------------------------------------------------------------------------From this, you may be able to see that:if A when divided by C has remainder Ra; andif B when divided by C has remainder Rb; then(A + B) divided by C will have remainder equal to the remainder of (Ra + Rb) divided by C

When n=30, 3n-1 = 89 .

3n+1=7 3*2+1=7

The Series has the formula 3n + 1/2(n - 1)(n - 2) = 3n + 1/2(n2 - 3n + 2) which simplifies to, 1/2(n2 +3n + 2)

Let n be the number, then: 1/n - 1/3n = 1/6 Solve the subtraction on the left: 1/n - 1/3n = 3/3n - 1/3n = 2/3n But we know this is 1/6, thus: 2/3n = 1/6 ⇒ 3n = 12 ⇒ n = 4 Thus the number is 4.

Nothing. If n is 2, 3n - 1 is 5 and 5 is prime.

79=1+3n79-1=1-1+3n78=3n78/3=3n/326=nn=26

Just plug in 30 for n in 3n-1. The answer is 89.

n/6 = 1/3. Cross-multiply : 3n = 6 so n = 2

Is it a. 3n square and 3n ans. 3n b. 3n *2 and 3n ans.3n ans. 3n for both!!

(3n + 15) / 2

No. 3n is not a factor of 3n + 7.

The two terms of 3N plus 1 would be 1st and 2nd. This is a math problem!😎

Divide each term in the numerator and denominator by the dominant term in the expression, which is n. Thus4n/(3n - 1) = 4/(3 - 1/n) As n tends to infinity, 1/n tends to zero and so the original expression tends to 4/(3 - 0) = 4/3.

4

No. 3n is not a factor of 3n + 7.

Study guides